Barthes: the beginning - Villacañas Berlanga, José Luis (Escritura e Imagen, 2021)
This paper offers an analysis of the dialectic of the concepts pleasure (plaisir) and jouissance in the trajectory of Roland Barthes. Torn between these two terms that had to be activated in the text, his entire theory depended on a neutral dialectic between them that showed the affinity between pleasure and the mandarinate of reading, and that left the paper for an unprecedented revolution for jouissance. The study shows how the game between the two terms leads to a difficult position to maintain, which led its author to propose in Sade, Fourier, Loyola a way of repeating excess and entering the zero point of meaning, a formal repetition, without content and without end, but also pleasant.
Keywords: Roland Barthes; Pleasure; Jouissance; Repetition; Culture; Text